2005
DOI: 10.1002/jhet.5570420601
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of 4-oxo-4H-1-benzopyran-3-carbonitrile

Abstract: The review article, primarily designed to complement an earlier one (J. Heterocycl. Chem. 2005Chem. , 42, 1035Chem. -1042, gives a comprehensive survey of the synthesis and chemistry of the title nitrile covering the literature published during 2005-2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…1 H and 13 C NMR spectra were recorded on a Bruker DRX 400 and Bruker Avance II spectrometers in DMSO d 6 (400 and 100 MHz, respectively) with Me 4 Si as an internal standard. Solvents were purified ac , 1 H, H(4)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H and 13 C NMR spectra were recorded on a Bruker DRX 400 and Bruker Avance II spectrometers in DMSO d 6 (400 and 100 MHz, respectively) with Me 4 Si as an internal standard. Solvents were purified ac , 1 H, H(4)).…”
Section: Methodsmentioning
confidence: 99%
“…1 Recently, 2 we have shown that the reaction of 3 cyanochromones 1 with primary aromatic and aliphatic amines begins from the attack on the unsubstituted atom C(2) and is accompa nied by the pyrone ring opening, that leads to the forma tion of a mixture of Z and E 3 aryl/alkylamino 2 (2 hydroxyaroyl)acrylonitriles 2, which readily and irrevers ibly cyclize to 2 amino 3 (aryl/alkyliminomethyl)chrom ones 3 (Scheme 1).…”
mentioning
confidence: 97%
“…1 Ibrahim 15 prepared the carboxamide 10 by treatment of a suspension of 3-formylchromone in carbon tetrachloride with NBS under UV irradiation followed by evaporation of the solvent and quenching the reaction mixture with ammonia, and subjected it to various transformations (Scheme 3). Thus, carboxamide 10 with aqueous NaOH (1M) rearranges to 4-hydroxycoumarin 12 via 11, with RNH 2 (R = Me, Et) in ethanol the 4-aminomethylenecoumarin 13, and with MeONa the azaxanthone derivative 14.…”
Section: Transformation Of the Nitrile Group Of 3-cyanochromonementioning
confidence: 99%
“…Being essentially gem activated alk enes (simultaneously α,β unsaturated ketones and ni triles), 3 cyanochromones 1 exhibit a variety of proper ties and can undergo additional transformations through opening of the γ pyrone ring and heterocyclizations at the carbonyl or cyano group because of the presence of a good leaving group (phenolate anion). 9 For instance, when treated with morpholine in aqueous DMF, 10 with n propylamine in ethanol, 11 or with aqueous NaOH, 6 chromone 1 easily undergoes recyclization into 2 ami no 3 formylchromone 2 and acts as its chemical equi valent in reactions with active methylene compounds. 9 However, data on reactions of 3 cyanochromones 1 with primary amines are very scarce.…”
mentioning
confidence: 99%
“…9 For instance, when treated with morpholine in aqueous DMF, 10 with n propylamine in ethanol, 11 or with aqueous NaOH, 6 chromone 1 easily undergoes recyclization into 2 ami no 3 formylchromone 2 and acts as its chemical equi valent in reactions with active methylene compounds. 9 However, data on reactions of 3 cyanochromones 1 with primary amines are very scarce. It has been only report ed 12 that reactions of 3 cyanochromone and 3 cyano 6 methylchromone with p toluidine yield equilibrium mix tures of an open chain tautomer (amino enone 3) and two cyclic tautomers 4 and 5 (Scheme 1).…”
mentioning
confidence: 99%